Innovative solutions for forming lingual and digital competence in the process of foreign language communication activity (Eurasian Journal of Philology Science and Education, 2024)
This article discusses the transformation processes of foreign language teaching with the aim ofdeveloping linguistic and digital competence among students of language specialties in the context ofdigitalization. The authors substantiate the need to develop this competence among students – futureteachers of foreign languages within the framework of a multilingual learning model using modern digitaltechnologies from web 0.1 to web 0.4 in different languages.The purpose of the study is to study ways of developing linguistic and digital competence amongstudents of language specialties in the context of digital literacy and professionally oriented learning. Theobject of the study is the methodology of foreign language education in the conditions of digitalisation;the subject of the study is the linguodigital competence formed in students during foreign language communicative activity. The article presents the results of a review of scientific literature within the framework of the research topic and proves the effectiveness of the methodology for developing linguistic anddigital competence in the process of foreign language learning. The proposed tools include the use of social networks, multimedia learning platforms and applications, audio and video resources that helpincrease motivation to learn foreign languages. These digital resources were successfully tested as partof the undergraduate educational program in the specialty “6B01704 – Foreign language: two foreignlanguages”. The proposed resources, according to the authors, are one of the most effective tools fordeveloping students’ linguistic and digital competence in the process of teaching a foreign language inthe new global digital reality.Key words: linguodidactics, foreign language competence, linguodigital competence, foreign language communicative activity, modernization of education, digital technologies.